Data on visitation records from wild bees and plants along a land use gradient in Germany and Belgium: laboratory work and protocol description for barcodingBiodiversity Exploratories - Maria Alejandra Parreño; Susanne Werle; Louella Buydens; Joshua Spitz; Franz Härtl; Jeremias Montoya; Fabian Ruedenauer; Baturalp Arisoy; Regina Seiler; Clementine Leroy; Qingming Feng-Spitz; Carmen Alexandra Nebauer; et al. (Data in Brief)
The dataset contains information on plant-bee interactions in an agricultural landscape with diverse intensities of land use management, in Germany and Belgium. It was collected during spring and early summer in 2020 and 2021 using two complementary types of sampling: standardized transects (5 transects of 50 m long in 1 h of netting) and targeted sampling in which flowers were observed for diverse periods of times, anywhere in an area of 50 to 150 m2. The species identity was obtained with field keys and DNA barcoding. The dataset is of use for building pollinator networks and in combination with other datasets on environmental characteristics of the area to better understand species distributions and interactions. Indeed, we include in the dataset information on environmental parameters from the plots of sampling (spatial coordinates, land use intensity index, landscape heterogeneity index, plant diversity), which can support further correlational analyses.